Evaluation of ELectrolytes in Adult Patients with Acute Leukemia before and after Chemotherapy (Baghdad Science Journal, 2013)
Abstract:Leukemia is a cancer of early blood forming cells. Most of them are cancers of white blood cells , however some leukemias start in other blood cell types.Electrolytes have modulatory effects on several biological mechanisms in the body namely as stabilizers,element of structures, essential element for hormonal function and also co-factors for a number of enzymes.In this study serum electrolytes levels were measured in patients with acute leukemia (AL) disorders before and after chemotherapy(anthracycline, doxorubicin, cytarabine ,prednisone, vincristine and doxorubicin) during one month and compared with that of control group. Blood samples were obtained from (43) patients (28 males and 15 females) aged (15-55)years;juset before and after chemotherapy. The control group contained samples from (40) healthy volunteers (26 males and 14 females) aged (15-55) years.Serum electrolytes levels(sodium Na+1,potassium K+1,calcium Ca+1,chloride Cl-1,magnesium Mg+2and phosphate PO4-3) were estimated using flame atomic absorbtion photometry. Serum levels of Na, K,Ca and Cl were significantly decreased in patients before chemotherapy in comparasion with that of control group. The mean concentration of serum phosphoruse and magnesium in acute leukemia patients was non significant compared with that of control group. In this study, determination of serum electrolytes in leukemic patients indicates an abnormal metabolic process in these patients